Rancang Bangun Sistem Penjadwalan Kursus Musik Berbasis Website - Wijanarko, Arief; Mailoa, Evangs (Smart Comp :Jurnalnya Orang Pintar Komputer, 2023)
Salatiga Music Course is an institution that manages teaching and learning activities in terms of music and choir activities. So far, Salatiga Music Course institution in carrying out attendance and transaction activities is still done manually with a notebook so that problems occur such as frequent errors in the process of recording attendance and transactions caused by human error. Therefore, this study aims to provide a solution from problem that occurred with designing and building a website-based music course system. This music course system is designed using the waterfall method and built with the PHP programming language using the laravel framework and MySQL database. This music course system is expected can reduce human error so that it can increase effectiveness and efficiency in the attendance and transaction process and increase institutional performance.